Comparison of Literacy Screener Risk Selection Between English Proficient Students and English Learners. (May 2021) - Cummings, Kelli D.; Smolkowski, Keith; Baker, Doris Luft
Universal screening is a critical component of school-based prevention systems. Screening data enable educators to target students for supplemental intervention, align resources to meet needs, and identify students who may be at risk for learning disabilities. One major requirement of the screening process is that all students are included to gain an accurate picture of school performance. It is therefore surprising that few evaluations of screening systems have focused on English language measures and their use with English learners. In this article, we aim to evaluate common screening thresholds, 54 across Grades k–3, to determine the extent to which they may differ between English learners and English proficient students. Results indicate that many thresholds are consistent between groups with some exceptions in kindergarten. We discuss implications for screening assessment and decision making but suggest that similar cut scores across groups do not imply similar intervention strategies.